2010
DOI: 10.1158/0008-5472.can-10-0578
|View full text |Cite
|
Sign up to set email alerts
|

Zoledronic Acid Potentiates mTOR Inhibition and Abolishes the Resistance of Osteosarcoma Cells to RAD001 (Everolimus): Pivotal Role of the Prenylation Process

Abstract: Despite recent improvements in therapeutic management of osteosarcoma, ongoing challenges in improving the response to chemotherapy warrants new strategies still needed to improve overall patient survival. In this study, we investigated vivo the effects of RAD001 (Everolimus®), a new orally available mTOR inhibitor, on the growth of human and mouse osteosarcoma cells either alone and in combination with zoledronate (ZOL), an osteoporesis drug which is used to treat bone metastases. RAD001 inhibited osteosarcom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 43 publications
2
75
0
Order By: Relevance
“…Notably, pretreatment with ZOL significantly reversed the CDDP resistance of NPC cells. This chemosensitization effect may have been due to ZOL inducing S phase cell cycle arrest, following a decrease in the percentage of cells in the G0/G1 phase and subsequent promotion of apoptosis, consistent with previous reports (17)(18)(19)25,27). The lower percentage of CDDP-resistant HNE1 cells in the G0/G1 phase may indicate a reduced capacity for DNA damage repair, which is considered a mechanism to overcome drug resistance.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Notably, pretreatment with ZOL significantly reversed the CDDP resistance of NPC cells. This chemosensitization effect may have been due to ZOL inducing S phase cell cycle arrest, following a decrease in the percentage of cells in the G0/G1 phase and subsequent promotion of apoptosis, consistent with previous reports (17)(18)(19)25,27). The lower percentage of CDDP-resistant HNE1 cells in the G0/G1 phase may indicate a reduced capacity for DNA damage repair, which is considered a mechanism to overcome drug resistance.…”
Section: Discussionsupporting
confidence: 89%
“…Among the chemotherapeutic agents, ZOL has exhibited promising sensitizing activity to be used in combination with chemotherapy and radiotherapy for cancer treatment (17)(18)(19). Notably, ZOL exhibited excellent activities against drug-resistant cancer cells (25,26). The present study investigated the effects of a low concentration of ZOL on CDDP-resistant NPC cells; the low dose was selected as the peak plasma levels of ZOL was 1-2 µM (17).…”
Section: Discussionmentioning
confidence: 99%
“…RAD001) only showed cytostatic activity, without inducing osteosarcoma cell death. 31 Indeed, protein synthesis, which is required for cell growth and cell cycle progression, is regulated by mTORC1, while PI3K-Akt as well as mTORC2 activation is also important for cell survival. 32,33 Interestingly, in consistent with recent studies, 34,35 we found that NVP-BEZ235 caused increased phosphorylation of MEK/Erk, although it appeared to be less significant compared with mTOR or PI3K inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Four-week-old male C3H/He mice were anesthetized as described previously before they were inoculated subcutaneously with a POS-1 cell suspension containing 2 Â 10 6 cells in the hind footpad. 29 Under these conditions, mice develop a primary tumor at the site of injection in 3 weeks that can be transplanted to mice of the same strain as a small fragment (2 Â 2 Â 2 mm) in close contact with the tibia. For this purpose, the periosteum of the diaphysis was opened and resected along a length of 5 mm, and the underlying bone was kept intact.…”
Section: In Vivo Experimentsmentioning
confidence: 99%